(untitled) (Experimental biology, 2016)
The article presents the results of a study biological features Ғ1 hybrid plants obtained in 2013 on the basis of fertile. Identified heterosis effect among hybrid plants biometric indicators such as plant height, number of internodes above ground, width and length of the sheet and the raw biomass. In hybrid plants during the growing season was longer compared to parental forms. In the course of this work is set heterosis phenomenon of hybrid plants obtained on the basis of fertile Ғ1 (♀SST Kaz-3 x ♂Larets, ♀Larets x ♂Oranzhevoe 160), exceeding the parental forms on economically valuable traits. These hybrids can then be used as a source of breeding material.